Advances in Peritoneal Surface Oncology - González-Moreno, S.; González-Moreno, S. (Recent Results in Cancer Research,, 2007)
S. González-Moreno (Ed. ) Advances in Peritoneal Surface Oncology With 45 Figures in 57 Separate Illustrations, 12 in Color and 19 Tables 123 IV Preface Santiago González-Moreno, MD, PhD Department of Surgical Oncology Centro Oncológico MD Anderson International España Calle Gómez Hemans 2 28033 Madrid Spain sgonzalez@mdanderson. es Library of Congress Control Number: 2006937141 ISSN 0080-0015 ISBN 978-3-540-30759-4 Springer Berlin Heidelberg New York This work is subject to copyright. All rights are reserved, whether the whole or part of the material is concerned, speci? ?cally the rights of translation, reprinting, reuse of illustrations, recitations, broadcasting, reproduction on micro? ?lm or in any other way, and storage in data banks. Duplication of this publication or parts thereof is permitted only under the provisions of the German Copyright Law of September 9, 1965, in its current version, and permission for use must always be obtained from Springer-Verlag. Violations are liable for prosecution under the German Copyright Law. Springer is part of Springer Science+Business Media http//www. springer. com Springer-Verlag Berlin Heidelberg 2007 Printed in Germany The use of general descriptive names, trademarks, etc. in this publication does not imply, even in the absence of a speci? ?c sta- ment, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. Product liability: The publishers cannot guarantee the accuracy of any information about dosage and application contained in this book. In every case the user must check such information by consulting the relevant literature.